Clinical outcomes during anticoagulant therapy in fragile patients with venous thromboembolism. Issue 2 (4th September 2017) - Moustafa, Farès; Giorgi Pierfranceschi, Matteo; Di Micco, Pierpaolo; Bucherini, Eugenio; Lorenzo, Alicia; Villalobos, Aurora; Nieto, José A.; Valero, Beatriz; Sampériz, Ángel L.; Monreal, Manuel
Abstract: Essentials Recent randomized trials suggested fewer bleeding events in fragile patients with VTE receiving DOACs. The frequency, clinical characteristics and outcome of these patients have not been reported in real life. Fragile patients with VTE had a higher risk for major bleeding or death and a lower risk for recurrences than non‐fragile. Background: Subgroup analyses from randomized trials suggested favorable results for the direct oral anticoagulants in fragile patients with venous thromboembolism (VTE). The frequency and natural history of fragile patients with VTE have not been studied yet. Objectives: To compare the clinical characteristics, treatment and outcomes during the first 3 months of anticoagulation in fragile vs non‐fragile patients with VTE. Methods: Retrospective study using consecutive patients enrolled in the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry. Fragile patients were defined as those having age ≥75 years, creatinine clearance (CrCl) levels ≤50 mL/min, and/or body weight ≤50 kg. Results: From January 2013 to October 2016, 15 079 patients were recruited. Of these, 6260 (42%) were fragile: 37% were aged ≥75 years, 20% had CrCl levels ≤50 mL/min, and 3.6% weighed ≤50 kg. During the first 3 months of anticoagulant therapy, fragile patients had a lower risk of VTE recurrences (0.78% vs 1.4%; adjusted odds ratio [OR]: 0.52; 95% confidence intervals [CI]: 0.37‐0.74) and a higher risk of major bleeding (2.6% vs 1.4%; adjusted OR: 1.41; 95% CI: 1.10‐1.80), gastrointestinal bleeding (0.86% vs 0.35%; adjusted OR: 1.84; 95% CI: 1.16‐2.92), haematoma (0.51% vs 0.07%; adjusted OR: 5.05; 95% CI: 2.05‐12.4), all‐cause death (9.2% vs 3.5%; adjusted OR: 2.02; 95% CI: 1.75‐2.33), or fatal PE (0.85% vs 0.35%; adjusted OR: 1.77; 95% CI: 1.10‐2.85) than the non‐fragile. Conclusions: In real life, 42% of VTE patients were fragile. During anticoagulation, they had fewer VTE recurrences and more major bleeding events than the non‐fragile.